2012
DOI: 10.1590/s1415-47572012005000062
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of South American samples reveals new population structuring of the blacktip shark (Carcharhinus limbatus) in the western Atlantic

Abstract: Carcharhinus limbatus has a cosmopolitan distribution and marked genetic structuring, mainly because of its philopatric behavior. However, analysis of this structuring has not previously included South American populations. In the present study, we analyzed a sample of adult individuals collected on the northern coast of Brazil and compared the sequences of the mitochondrial control region with those of populations already genotyped. Relatively high haplotype diversity (12 haplotypes, genetic diversity of 0.79… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 52 publications
3
20
0
Order By: Relevance
“…, ; Keeney and Heist ) and rectangles (Sodré et al. ). CL 1– CL 4 are identical to Indian Ocean and Indo‐Pacific haplotypes discovered by Keeney and Heist ().…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…, ; Keeney and Heist ) and rectangles (Sodré et al. ). CL 1– CL 4 are identical to Indian Ocean and Indo‐Pacific haplotypes discovered by Keeney and Heist ().…”
Section: Resultsmentioning
confidence: 99%
“…(, ), Keeney and Heist (), and Sodré et al. () for C. limbatus ; Giles et al. () for C. sorrah ; and Duncan et al.…”
Section: Methodsmentioning
confidence: 96%
“…Pronounced structuring was detected between African (KwaZulu‐Natal and Sierra Leone) and Indo‐Pacific populations and those of the eastern Atlantic based on mitochondrial DNA (mtDNA) (Keeney & Heist, ). However, this analysis did not include any South American populations, which were tested later and revealed that C. limbatus from northern Brazil is genetically distinct from the previously studied populations (Sodré et al., ). The aim of this study was to unravel patterns of connectivity among stocks of these two commercially exploited species along the coasts of the Arabian Peninsula, Pakistan, and KwaZulu‐Natal, South Africa (hereafter referred to as South Africa), to facilitate regional conservation and management.…”
Section: Introductionmentioning
confidence: 98%
“…Dudgeon et al 2009;Ovenden et al 2009;Feldheim et al 2010;Geraghty et al 2013). Population genetic structure can range from, for example, basking sharks that display little genetic differentiation over ocean basins globally (Hoelzel et al 2006) to blacktip sharks that show significant structure over small, regional scales (Keeney et al 2005;Sodré et al 2012). At present, carcharhinids have the greatest representation in the phylogeographic literature, as many of these species are of economic importance in commercial, recreational and artisanal fisheries (Dudgeon et al 2012).…”
Section: Population Structure Assessment For Shark Fisheries Managementmentioning
confidence: 99%
“…In sharks, genetic variation is known to be low, with mitochondrial sequence evolution estimated to be six to eight times slower than that of mammals (Martin et al 1992). Despite this, a number of studies have been successful in assessing population differentiation in sharks using a portion of the mitochondrial control region (mtCR) (Keeney et al 2005;Keeney and Heist 2006;Duncan et al 2006;Chabot and Allen 2009;Sodré et al 2012). Microsatellites, or simple sequence repeats (SSRs), have also been used and these highly variable short, tandem repeat DNA sequences have proven to be ideal for fine-scale stock structure investigations relevant to short-term fisheries management in sharks (Dudgeon et al 2012).…”
Section: Molecular Tools For Population Structure and Demographic Assmentioning
confidence: 99%